The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14194198
|View full text |Cite
|
Sign up to set email alerts
|

Higher Total Cholesterol Concentration May Be Associated with Better Cognitive Performance among Elderly Females

Abstract: Background: The brain contains the highest level of cholesterol in the body, and the total amount of serum cholesterol in the blood has a huge impact on brain aging and cognitive performance. However, the association of total serum cholesterol with cognitive function remains uncertain. This study determines whether there is an association between the total amount of cholesterol in the blood and cognitive performance in elderly females without a history of stroke. Methods: This population-based cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 71 publications
(73 reference statements)
2
19
0
Order By: Relevance
“…To date, evidences for the association between TC levels and cognitive function were conflicting. Some studies reported that TC levels were negatively, positively, or not associated with cognitive impairment 14–16,19,20,23,24 . Our results on the association between TC and cognition were consistent with several studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To date, evidences for the association between TC levels and cognitive function were conflicting. Some studies reported that TC levels were negatively, positively, or not associated with cognitive impairment 14–16,19,20,23,24 . Our results on the association between TC and cognition were consistent with several studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our results on the association between TC and cognition were consistent with several studies. A more recent study suggested that higher TC levels were statistically associated with improved cognitive function among females over 60 years old 14 . Research based on a representative sample of participants aged 70 years and older revealed that both lower TC levels and decreased TC levels were related to relatively poorer cognition 15 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, a meta-analysis showed that there was no clear consistent relationship between cholesterol and cognitive decline ( Peters et al, 2021 ). Furthermore, some studies have demonstrated that a higher concentration of TC might be a protective factor for cognitive performance ( Lv et al, 2016 ; Pang et al, 2022 ). Therefore, further experiments are needed to identify the correlation between serum TC and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%